METODE AL-KHAZIN DALAM TAFSIR ‚LUBAB AL-TA'WIL FI MA'ANIAL-TANZIL - Mojiburrohman, Mojirrohman (Fakultas Agama Islam Universitas Islam Madura, 2019)
Reviewing the paper the books of Tafsir to find the true form and its type. Absolutely, it is not far from the scientific characteristics owned by the author himself. Therefore, the study in the writing of this paper is more focus on reading the first creator, it will automatically provide on what works have been produced and distributed in social life.characteristics of Al-Kha > Zin in the Luba > b Al-Ta'wi > L fi > Ma'a > Ni > Al-Tanzi > L are part of the component in discovering and determining the tendency found in the work. Based on the quantity of an al-Kha > Zin by pointing to the history of the personality of his life, the interpretation will be assessed by one aspect, which will then be concentrated on the subjective value. However, if it is based on the quality of al-Kha > Zin with a composition of the science that is quite a portion of course the value contained in the work is more regarded as objective by holding on to methodical and theoretical analysis.